Limitasi Domain Kognisi dan Perilaku dalam Pembentukan Karakter: Tinjauan Sufistik Pendidikan Islam - Hajiannor, Hajiannor; Cahyadi, Ani; Setiawan, Agus (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
This article aims to analyze the character through the domain of cognition and behavior. That the domain of cognition and behavior consists of three domains of intelligence; Cognitive, affective and psychomotor play an important role in shaping personality. However, it should be realized that each domain has a specific function in stimulating the pattern of autonomous psychological traits. The method used is qualitative analysis based on critical analysis approach. The results of the study show that there are various patterns of individual character in thinking, acting and acting. Observing the existence of function limitations, it is necessary to balance the internal domains, harmonize and synergize them with other domains. This is intended so that the internalization of positive values ​​instilled in each domain for the formation of good character can be carried out in a directed, simultaneous and optimal manner. Full awareness (conscious awareness) thinking activities that are connected through the work function of the brain can basically build connectedness and influence each other between domains in shaping behavior. Its optimization requires harmonization between body and spirit, mind and heart, knowledge and charity. With it, the intellectual clarity that a person has is not only in the normative-idealistic but empirical-applicative aspects. Ihsan, who has a core of moral values, is able to move conscious awareness while still standing on his strong individuality to also bring benefits among others, including relationships with his natural environment.